2000
DOI: 10.1007/s100720070113
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends of stroke in Valle d'Aosta, Italy. Incidence and 30-day fatality rates

Abstract: The objective of this study was to evaluate temporal changes of stroke in an Italian community by comparing the present incidence rates with those reported in the same area for 1989. The two studies were conducted by the same research group and met almost all the criteria proposed for an "ideal" stroke incidence study. The annual incidence rate per 1000 inhabitants increased (p < 0.01) by 29%, from 2.23 (95% CL, 1.96-2.50) in 1989 to 2.89 (95% CL, 2.58-3.20) in 1997. No statistically significant change was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…Eighteen studies reported incidences for men and women separately 5 9 10 17 18 20 22 27 29 35 44 45 47 49 50 52 54 57. The overall incidence in this subset of studies was 10.5 (95% CI 9.9 to 11.2) per 100 000 person-years; the incidence for men was 9.2 (95% CI 8.4 to 10.2) and for women 11.5 (95% CI 10.6 to 12.6).…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen studies reported incidences for men and women separately 5 9 10 17 18 20 22 27 29 35 44 45 47 49 50 52 54 57. The overall incidence in this subset of studies was 10.5 (95% CI 9.9 to 11.2) per 100 000 person-years; the incidence for men was 9.2 (95% CI 8.4 to 10.2) and for women 11.5 (95% CI 10.6 to 12.6).…”
Section: Resultsmentioning
confidence: 99%
“…In particular in the 1989–1997 interval an increase in stroke incidence was reported [29]: ageing of the population and better cases identification could explain the higher incidence rate. In a previous study (2004–2005) we reported a major reduction in the incidence of stroke (29 %) between 1989 and 2004–2005 [12].…”
Section: Discussionmentioning
confidence: 99%
“…These registers started for different purposes; they were basically prospective studies aiming at estimating the impact of stroke, understanding variation in the quality of care and outcome after stroke, and answering issues related to case mix and stroke health care, quality factors on the variations in health of stroke patients. Attack rates from the Italian register appeared, for the common age range, to be lower than those registered in the Aosta Valley region (men: 38/10,000 in the age range 55–64 and 98/10,000 in the upper one; women: 18/10,000 and 63/10,000 in the two age ranges, respectively) [6] and in the city of l’Aquila (men: 29/10,000 in the age range 55–64 and 97/10,000 in the upper decade; women: 17/10,000 and 70/10,000, respectively) [7]. …”
Section: Discussionmentioning
confidence: 99%
“…In the late 1990s, experiences were documented in Italy in the Aosta Valley region [6] and in the city of l’Aquila [7, 8], where registers including in- and out-of hospital events were implemented. Hospitalized events in these areas were collected; then severity and outcome were assessed through a detailed morbidity and mortality follow-up.…”
Section: Introductionmentioning
confidence: 99%